Математическая модель биотического круговорота в озёрной экосистеме - Умнов, А.А. (Гидробиологический журнал, 1972)
Построена математическая модель пелагической озерной экосистемы, состояние которой определяется биомассой фито- и зоопланктона, количеством мертвого органического вещества начальной стадии разложения, стойкого органического вещества, биогенных элементов, растворенных в воде и находящихся в перечисленных компонентах экосистемы. Сравнение полученных данных с результатами исследования экосистемы оз. Мястро показало пригодность созданной модели для описания динамических процессов, протекающих в озерных экосистемах. Модель использована для выяснения влияния концентрации биогенных элементов на сезонную динамику биомасс и продукций фито- и зоопланктона. A mathematic model of pelagic lake ecosystem is proposed. The state of the ecosystem is determined by phyto- and zooplankton biomass, quantity of the dead organic substance, quantity of stable organic substance (in the given model dead organic substance is considered together with bacterioplankton), quantity of biogenic elements, dissolved in water and taking part in the ecosystem components enumerated above. The role of an external factor for an ecosystem play solar radiation and the thermal regime. The comparison of modelling results with those obtained in the study of ecosystem of the Mastro lake showed the good reliability of the model for description of dynamic processes in the lake ecosystems. The model have been used for study of effects of biogenic elements concentration of the seasonal biomass dynamics and the zoo- and phytoplankton productivity.